High Mobility Group Box-1: A Missing Link between Diabetes and Its Complications - Han Wu; Zheng Chen; Jun Xie; Li-Na Kang; Lian Wang; Biao Xu (Hindawi Limited, 2016)
High mobility group box-1 (HMGB-1), a damage-associated molecular pattern, can be actively or passively released from various cells under different conditions and plays a pivotal role in the pathogenesis of inflammation and angiogenesis-dependent diseases. More and more evidence suggests that inflammation, in addition to its role in progression of diabetes, also promotes initiation and development of diabetic complications. In this review, we focus on the role of HMGB-1 in diabetes-related complications and the therapeutic strategies targeting HMGB-1 in diabetic complications.